PAH-pollution effects on sensitive and resistant embryos: Integrating structure and function with gene expression. - Goran Bozinovic; Damian Shea; Zuying Feng; David Hinton; Tim Sit; Marjorie F Oleksiak (PLoS ONE)
Polycyclic aromatic hydrocarbons (PAHs) are among the most widespread natural and anthropogenic pollutants, and some PAHs are proven developmental toxicants. We chemically characterized clean and heavily polluted sites and exposed fish embryos to PAH polluted sediment extracts during four critical developmental stages. Embryos were collected from Fundulus heteroclitus populations inhabiting the clean and heavily polluted Superfund estuary. Embryos of parents from the clean sites are sensitive to PAH pollutants while those of parents from the heavily polluted site are resistant. Chemical analysis of embryos suggests PAH accumulation and pollution-induced toxicity among sensitive embryos during development that ultimately kills all sensitive embryos before hatching, while remarkably, the resistant embryos develop normally. The adverse effects on sensitive embryos are manifested as developmental delays, reduced heart rates, and severe heart, liver, and kidney morphological abnormalities. Gene expression analysis of early somitogenesis, heartbeat initiation, late organogenesis, and pre-hatching developmental stages reveals genes whose expression significantly differs between sensitive and resistant embryo populations and helps to explain mechanisms of sensitivity and resistance to polluted environments during vertebrate animal development.